Formulation and Antibacterial Activity Testing of Eco-Soap Based on Sodium Lauryl Sulfate Surfactant - Widiani, Nurhaida; Novitasari, Aulia; Winandari, Ovi Prasetya; Saputri, Dwijowati Asih (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Pineapple is a fruit that is often used only for its flesh, while the skin remains waste. As a form of dealing with pineapple waste, one way is to use it as an eco-enzyme. Making soap with added eco-enzyme can be used as an alternative for washing dishes. Therefore, this research aims to determine the formulation and test the antibacterial activity of eco-soap based on the surfactant Sodium Lauryl Sulphate. This research is experimental research, which was carried out in July-October 2023. The research results showed that the pH of eco-Soap was 3.46; foam height 1.5 cm; viscosity testing 14.9 mPas; fatty acids 1.44%; and 6 mm antibacterial activity testing. Based on the research results, it was concluded that the surfactant-based eco-soap formulation had good stability in the eco-soap foam height test. The diameter of the zone of inhibition of eco-soap's antibacterial activity showed that bacterial inhibition was moderate.